The entire picture is needed to solve. the bottom of the pic is cut off
Answer:
As x goes to negative infinity, g(x) goes to zero.
As x goes to positive infinity, g(x) goes to zero.
(So the answer is the second option)
Step-by-step explanation:
We have the function ![g(x)=\frac{1}{x^2}](https://tex.z-dn.net/?f=g%28x%29%3D%5Cfrac%7B1%7D%7Bx%5E2%7D)
First, let's look at what happens when we input smaller and smaller numbers
![g(-10)=\frac{1}{100} \\\\g(-100)=\frac{1}{10000}](https://tex.z-dn.net/?f=g%28-10%29%3D%5Cfrac%7B1%7D%7B100%7D%20%5C%5C%5C%5Cg%28-100%29%3D%5Cfrac%7B1%7D%7B10000%7D)
As we can see, as we input smaller and smaller numbers, the answer gets smaller.
Eventually, these fractions will be so small that they will get closer and closer to zero.
This same thing applies to larger and larger numbers, so the end behavior of each side will both be zero.
Answer:
Step-by-step explanation:
At this price, the store sells 100 men's hats per week. The owner estimates that for every $1 increase in price, one fewer men's hat is sold per week
Answer:
Theres no picture?
Step-by-step explanation:
Answer:
![x^2+18=-9x : x = -3, x = -6](https://tex.z-dn.net/?f=x%5E2%2B18%3D-9x%20%3A%20x%20%3D%20-3%2C%20x%20%3D%20-6)
Step-by-step explanation:
![x^2+18=-9x](https://tex.z-dn.net/?f=x%5E2%2B18%3D-9x)
Add 9x to both sides:
![x^2+18+9x=-9x+9x](https://tex.z-dn.net/?f=x%5E2%2B18%2B9x%3D-9x%2B9x)
Simplify:
![x^2+9x+18=0](https://tex.z-dn.net/?f=x%5E2%2B9x%2B18%3D0)
Solve with the quadratic formula:
For a quadratic equation of the form
the solutions are:
![x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x_%7B1%2C%5C%3A2%7D%3D%5Cfrac%7B-b%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
For ![a=1,\:b=9,\:c=18:\quad x_{1,\:2}=\frac{-9\pm \sqrt{9^2-4\cdot \:1\cdot \:18}}{2\cdot \:1}](https://tex.z-dn.net/?f=a%3D1%2C%5C%3Ab%3D9%2C%5C%3Ac%3D18%3A%5Cquad%20x_%7B1%2C%5C%3A2%7D%3D%5Cfrac%7B-9%5Cpm%20%5Csqrt%7B9%5E2-4%5Ccdot%20%5C%3A1%5Ccdot%20%5C%3A18%7D%7D%7B2%5Ccdot%20%5C%3A1%7D)
![x =\frac{-9 + \sqrt{9^2-4\cdot \:1\cdot \:18}}{2\cdot \:1} : -3](https://tex.z-dn.net/?f=x%20%3D%5Cfrac%7B-9%20%2B%20%5Csqrt%7B9%5E2-4%5Ccdot%20%5C%3A1%5Ccdot%20%5C%3A18%7D%7D%7B2%5Ccdot%20%5C%3A1%7D%20%3A%20-3)
![x =\frac{-9 - \sqrt{9^2-4\cdot \:1\cdot \:18}}{2\cdot \:1} : -6](https://tex.z-dn.net/?f=x%20%3D%5Cfrac%7B-9%20-%20%5Csqrt%7B9%5E2-4%5Ccdot%20%5C%3A1%5Ccdot%20%5C%3A18%7D%7D%7B2%5Ccdot%20%5C%3A1%7D%20%3A%20-6)
The solution to the quadratic equation are:
![x=-3,\:x=-6](https://tex.z-dn.net/?f=x%3D-3%2C%5C%3Ax%3D-6)
Hope I helped. If so, may I get brainliest and a thanks?
Thank you, have a good day!